1992
DOI: 10.1172/jci116135
|View full text |Cite
|
Sign up to set email alerts
|

Impaired secretion of the elongated mutant of protein C (protein C-Nagoya). Molecular and cellular basis for hereditary protein C deficiency.

Abstract: Genetic analysis of a heterozygous protein C-deficient patient revealed a novel deletion of a single guanine residue ("'7G) among four consecutive guanine nucleotides [3Trp(TGG)-31Gly(GGT)j in exon IX, which encodes the carboxyl-terminal region of protein C. This deletion results in a frameshift mutation and substitution of the last 39 amino acids ("1Gly-419Pro) with 81 abnormal amino acid residues, and we have designated this elongated variant as Protein C-Nagoya. A mutagenic primer was designed which repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…All six clones from the patient contained this mutation. The mutation was identical to that reported by our group as protein C‐Nagoya ( Yamamoto et al , 1992 ; Katsumi et al , 1996 ). The 8857 deletion causes a frameshift of the transcribed protein C gene, replacing the carboxy‐terminal 39 amino acids with 81 abnormal amino acid sequences ( Yamamoto et al , 1992 ; Katsumi et al , 1996 ) .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…All six clones from the patient contained this mutation. The mutation was identical to that reported by our group as protein C‐Nagoya ( Yamamoto et al , 1992 ; Katsumi et al , 1996 ). The 8857 deletion causes a frameshift of the transcribed protein C gene, replacing the carboxy‐terminal 39 amino acids with 81 abnormal amino acid sequences ( Yamamoto et al , 1992 ; Katsumi et al , 1996 ) .…”
Section: Resultssupporting
confidence: 88%
“…B. DNA analysis of the family of the patient with homozygous protein C deficiency. A 234‐bp PCR fragment was amplified from each DNA sample with the mutagenic primers, as described previously ( Yamamoto et al , 1992 ). The fragment was digested by Ava I and subjected to 2% agarose gel electrophoresis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All mutations were previously reported in Japanese patients with protein C deficiency, except for c.439G [ A which had been already reported in 2 Dutch families [11][12][13].…”
mentioning
confidence: 97%
“…This could result in impaired transport across intracellular membranes by &dquo;chaperone&dquo; proteins(28,29). Indeed, several groups have performed in vitro protein translation studies with mutated protein C expression vectors and have found loss of secretion of the aberrant proteins(30,31). Presumably, in families C and H with type II deficiency there is still adequate protein secretion, but the amino acid substitution interferes with protein function.…”
mentioning
confidence: 99%